Kualitas Perangkat Pembelajaran Model Problem Based Learning dengan Pendekatan Contextual Teaching and Learning - Trisnawaty Junus Buhungo; Supartin Supartin; Asri Arbie; Dewa Gede Eka Setiawan; Abdulrahman Djou; Muhammad Yunus (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study was to describe the quality of physics learning tools using the Problem-Based Learning model with the Contextual Teaching and Learning approach on the material of elasticity and Hooke's law. The research was conducted at Muhammadiyah Batudaa High School, and the research sample used was class XI IPA1 using simple random sampling technique. This development research uses Research and Development (R&D) research with the ADDIE development model developed by Reiser and Mollenda which consists of the Analysis, Design, Development, Implementation and Evaluation stages. The results of the study show that the validation of the entire learning device is stated to be very valid. The practicality of learning devices is determined by the average percentage of the implementation of learning carried out during two meetings reaching 97.61% with very good criteria, then for teacher and student responses through questionnaires give positive responses. The effectiveness of learning devices is seen through student activity data which obtains an average percentage of 90.30% obtained very good criteria and student learning outcomes data on elasticity and Hooke's law show an increase in the N-gain value of 0.74 included in the high N-gain criteria. This study concludes that physics learning tools that use the Problem-Based Learning model with a Contextual Teaching and Learning approach on elasticity and Hooke's law are included in the valid, practical and effective criteria to be applied in the learning process in class.